Implementasi Model Pembelajaran Discovery Learning Pada Bidang Studi Pendidikan Agama Islam dan Budi Pekerti di Kelas V Sekolah Dasar - Slamet Echwani (JOSSE: Journal of Social Science and Economics, 2023)
This thesis is the result of field research (Field Research) to answer the first question: How to plan discovery learning models in the field of Islamic Studies and Budi Pekerti in class V SDI Nurul Bayan Kebunagung Sumenep?. and second: How is the implementation of the discovery learning model in the field of PAI and Budi Pekerti in class V SDI Nurul Bayan Kebunagung Sumenep?. This type of research is a type of qualitative research (field research), namely data collection carried out by research at the place where the phenomenon under study occurs. In this case, the authors collect data on issues related to the implementation of the discovery learning model in the field of Islamic religious education and character. This research is a descriptive exploratory research which aims to describe the state or status of the phenomenon. Based on the results of the study, it was found that the learning planning for Islamic Religious Education and Budi Pekerti using the discovery learning model can be stated in the syllabus and developed in the lesson plans made at the beginning of the new school year, which are tailored to the needs of students. So that it will obtain results that are in accordance with the competency objectives of PAI subjects, the RPP will be brought to the MGMPS and forwarded to the MGMP center/district. The implementation of Islamic religious education and character education using the discovery learning model can be carried out in three stages, namely preliminary activities to restore students' concentration in understanding the material (praying, reading verses of the Qur'an, attendance, apperception). Second, the core activity is discussing learning materials using the discovery learning model, by working in groups. Students are active in classroom learning, namely observing, identifying, processing data, proving data, and drawing conclusions. The third stage is the closing activity, the teacher provides reinforcement, prays together and continues with greetings.